Exploring retailer marketing strategies for value added bean products in Kenya - Nakazi, Florence; Babirye, Immaculate; Birachi, Eliud Abucheli; Ugen, Michael Adrogu (Brill, 2019)
Unlike many other Sub-Saharan African countries, for many years Kenya had comparative advantages in the manufacturing of processed bean products. However, for new competitors intending to join the bean processing industry, little is known about marketing strategies for value added bean products. Using data from 90 retailers in the Nairobi and Kiambu counties in Kenya, a two-step econometric procedure-multivariate probit and Poisson regression models were applied to analyse retailers’ marketing strategy decisions. Findings show that information sources, cost of marketing, supply modalities, price of products, and quantities handled significantly influenced retailers’ marketing strategy choice. Surveyed retailers applied varying marketing strategies to market value added bean products. There is need for prospective retailers to choose an appropriate mix of strategies to penetrate the dynamic market with a number of value added bean products, and promote local consumption of value added bean products